The Impact of Cryptocurrencies on Stock Exchange Development: Empirical Evidence on Canadian firms - Hanene, Ezzine; Ines, Abdelkefi; Aida, Smaoui; Sirine, Magdiche (Journal of Posthumanism, 2025)
Cryptocurrencies are decentralized digital currencies secured by blockchain technology. Their growing popularity has a significant impact on traditional financial markets. The purpose of this paper is to examine the impact of cryptocurrency investment on stock financial development. Our empirical evidence is conducted on (30) Canadian firms during the period August 2017- May 2023. The firms are the most important companies in the financial sector. The results of the VECM estimation show a positive and significative impact of Bitcoin Value on each variable assessing stock market development in long term as Market Liquidity, Market Size, Market Capitalization. In short term, this same relationship is observed with Market Size and Market Liquidity. Bitcoin value has a negative impact on Market Capitalization. The Exchange Rate and Unemployment Rate provide a negative and significant relationship towards stock market development in the long-term. In contrast, the short-term relationship results show that Exchange Rate acts positively only on the Market Capitalization. In contrast, Market Liquidity has a positive impact on the Exchange Rate. Moreover, we find the absence of the impact of Unemployment Rate on Stock Financial Development in short term. But, there is a significant and negative incidence of Market Liquidity and Market Size on Unemployment Rate. Our results demonstrate also the positive and significant impact of Unemployment Rate on Bitcoin Value.